HORMONAL EFFECTS ON HEALTH BIOMARKERS AND REPRODUCTIVE PERFORMANCE IN BUFFALOES (Bubalus bubalis) WITH LOW, MEDIUM AND HIGH MILK PRODUCTION - Shahid; Z. I. Qureshi; Zia-ur-Rahman (Journal of Animal and Plant Sciences, 2020)
This study was conducted to determine the effects of Bovine somatotropin (rbST) and oxytocin on various health biomarkers, reproductive performance and milk composition of buffaloes during spring and hot summer. A total of 60 Nili-Ravi buffaloes were randomly divided into three groups based on their milk production. Low (1-2.9 liters/milking), medium (3-5.9 liters/milking) and High (6-12 liters/milking), with (n=10) animals in each group during spring and summer. Animals of respective groups received recombinant bovine somatotropin (rbST) (Boostin-250 manufactured by LG Life Sciences, Ltd, South Korea and distributed by M/S Ghazi Brothers, Pakistan) 35mg on alternate days and oxytocin 10 IU before each milking, starting on day 70 postpartum till the end of lactation. Blood samples were collected to determine Total oxidant status (TOS), Total antioxidant capacity (TAC), Serum alanine aminotransferase (ALT) and Aspartate aminotransferase (AST). Milk samples were analyzed for fat, protein, lactose and SNF contents. Reproductive performance parameters were assessed by rectal palpation and from farm record. Results revealed that mean ALT, AST and TOS activity was significantly higher during summer. Milk production was very well correlated with their assigned groups of milk production during spring. Milk fat, protein and lactose contents decreased due to rbST, oxytocin or rbST+ oxytocin treatment. In conclusion during summer, milk yield was increased after rbST+ oxytocin treatment, but decreased following treatment with either hormone.
Keywords: milk production and composition; Somatotropin; Oxytocin; Nili-Ravi buffaloes; Seasons